Differential intervention outcomes among fathers who commit domestic and family violence: the influence of parental relationship status - Gatfield, Emma (Journal of family violence, 2025)
Background: In Western contexts, the behavior of domestically violent men is largely addressed through legal sanctions and standardised men’s behavior change programs. When domestically violent fathers remain together or in contact with their families, safety is an ongoing concern. However, program evaluations have failed to provide clear evidence for their effectiveness in addressing family violence in relation to parenting status. Part of the problem in developing efficacious programs has been the challenge of targeting them to typologies or socio-cultural needs of participants. Purpose: The Caring Dads (CD) program supports father-change through leveraging men’s motivation to be positive parents, promoting child-centred fathering and cessation of family abuse. The aim of this study was to investigate whether participating fathers improved their co-parenting interactions, family functioning and wellbeing, and considered father characteristics and relationship statuses that coincided with positive outcomes. Methods: This mixed method Australian study investigating a CD pilot incorporated psychological measures and semi-structured interviews at pre-, post- and 10 months post-intervention. Participants were fathers who attended CD in South-East Queensland, 2017-2019, and their co-parents. Results: All fathers experienced improvements in parenting and family functioning by post-intervention, with greatest improvements for partnered fathers’ families. Partnered fathers also experienced improved parental alliance, unlike most separated fathers, although results must be viewed with caution due to small sample size and attrition across the study duration. Conclusion: This study provides early support for improvements in CD participants’ fathering, parental alliance, and family functioning, most substantially for partnered fathers, though findings should be further investigated with larger cohorts.